Mineral nutrients in plants under changing environments: A road to future food and nutrition security - Khan, M. Iqbal R.; Nazir, Faroza; Maheshwari, Chirag; Chopra, Priyanka; Chhillar, Himanshu; Sreenivasulu, Nese (Wiley, 2023)
Plant nutrition is an important aspect that contributes significantly to sustainable agriculture, whereas minerals enrichment in edible source implies global human health; hence, both strategies need to be bridged to ensure “One Health” strategies. Abiotic stress‐induced nutritional imbalance impairs plant growth. In this context, we discuss the molecular mechanisms related to the readjustment of nutrient pools for sustained plant growth under harsh conditions, and channeling the minerals to edible source (seeds) to address future nutritional security. This review particularly highlights interventions on (i) the physiological and molecular responses of mineral nutrients in crop plants under stressful environments; (ii) the deployment of breeding and biotechnological strategies for the optimization of nutrient acquisition, their transport, and distribution in plants under changing environments. Furthermore, the present review also infers the recent advancements in breeding and biotechnology‐based biofortification approaches for nutrient enhancement in crop plants to optimize yield and grain mineral concentrations under control and stress‐prone environments to address food and nutritional security.